Limits of Freedom of Information Act in Brazil: theoretical reflections in the sphere of information science - Elias Borges, Ellen Valotta [UNESP]; Martinez-Avila, Daniel [UNESP]; Gomes de Mello, Mariana Rodrigues [UNESP] (Univ Federal Minas Gerais, Escola Biblioteconomia, 2020)
This paper aims to verify the applicability of the Freedom of Information Act (LAI) in Brazil. We conducted a comparative analysis of the proposal of the Law and its applicability by public organisms. We worked with the electronic Citizens' Enquiry Service (e-SIC) and the Federal Government website.. The information requests submitted to the competent law enforcement authorities allowed the analysis of the applicability of the Law. The results showed that there are wide great divergences regarding the content of the law. In addition, they also suggest that the discussions on information, when considering not only information access but also the appropriation of information, can contribute to social development. The consideration of information access and information appropriation in a complementary way may bring significant contributions to the scientific and social fields.
Keywords: Freedom of Information Act; Appropriation of information; Competent law enforcement Authorities; Electroniccitizens' enquiryservice